2016
DOI: 10.1016/j.slsci.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Associations of common chronic non-communicable diseases and medical conditions with sleep-related problems in a population-based health examination study

Abstract: A cross-sectional population-based survey, the National FINRISK 2012 Study, designed to monitor chronic diseases and their risk factors in Finland. A random sample of 10,000 adults aged 25–74 years, and of them, 64% (n=6424) participated the study. Participants subjectively reported the total durations for sleep and naps (n=6238), sleep quality (n=5878), bedtimes and wake-up times separately for working days and weekends yielding the amount of sleep debt (n=5878), and the seasonal variation in sleep duration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Of these, the associations of sleep features with depressive disorder remained significant after adjustment for multiple testing. Thus, this current finding, which emerged from the single-item analysis corroborated the earlier reports on the association of depressive disorder with sleep 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Of these, the associations of sleep features with depressive disorder remained significant after adjustment for multiple testing. Thus, this current finding, which emerged from the single-item analysis corroborated the earlier reports on the association of depressive disorder with sleep 39 .…”
Section: Discussionsupporting
confidence: 92%
“…Briefly, chronotype is the difference between your awake time and your self-selected awake time. The higher the chronotype, the more one needs to adjust his/her natural circadian rhythm, which can lead to health implications [ 42 , 43 ]. This recent finding could potentially explain why sedentary behavior impacts more health markers in youth than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is also largely influenced by diseases. Numerous studies have confirmed the close association between chronic noncommunicable diseases and the prevalence of sleep disorders [13,15]. Meanwhile, it has been shown that medicines used to treat diseases, such as cardiovascular drugs and antipsychotic drugs, have also been related to sleep status [23].…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, adverse effects on the body's immune and endocrine systems have been found to be due to sleep disorders [12]. According to related studies, sleep disturbances are closely related to cardiovascular diseases, [13] malignant tumors, [14] and other chronic noncommunicable diseases [15].…”
Section: Introductionmentioning
confidence: 99%